Synthesis of Graphene Oxide Interspersed in Hexagonal WO3 Nanorods for High-Efficiency Visible-Light Driven Photocatalysis and NH3 Gas Sensing - Salama, Tarek M.; Morsy, Mohamed; Abou Shahba, Rabab M.; Mohamed, Shimaa H.; Mohamed, Mohamed Mokhtar (Frontiers in Chemistry, 2019)
WO3 nanorods and GO (at 1wt% loading) doped WO3 were synthesized using a template free deposition-hydrothermal route and thoroughly characterized by various techniques including XRD, FTIR, Raman, TEM-SAED, PL, UV-Vis, XPS and N2 adsorption. The nanomaterials performance was investigated toward photocatalytic degradation of methylene blue (20 ppm) under visible light illumination (160 W, λ> 420) and gas sensing ability for ammonia gas (10-100 ppm) at 200oC. HRTEM investigation of the 1%GO.WO3 composite revealed clear WO3 nanorods of a major d-spacing value of 0.16 nm in accordance with the crystal plane (221); the relevant plane was absent in pure WO3 establishing the intercalation with GO. The MB degradation activity was considerably enhanced over the 1%GO.WO3 catalyst with a rate constant of 0.0154 min-1 exceeding that of WO3 by 15 times. The reaction mechanism was progressed depleting electrons, holes and •OH reactive species as determined via the characterization techniques and scavenger examination tests. The drop in both band gap (2.49 eV) and PL intensity was the main reason responsible for enhancing the photo-degradation activity of the 1%GO.WO3 catalyst. The later catalyzed two electron O2 reduction forming H2O2, which contributed as well in the photoactivity improvement via forming •OH. The hexagonal structure of 1%GO.WO3 showed a better gas sensing performance for ammonia gas at 100 ppm (Ra-Rg/Rg =17.6) exceeding that of pure WO3 nanorods (1.27). The superiority of the gas-sensing property of the 1%GO.WO3 catalyst was mainly ascribed to the high dispersity of GO onto WO3 surfaces by which different carbon species served as mediators to hinder the recombination rate of photo-generated electron-hole pairs and therefore facilitated the electron transition. The dominancy of the lattice plane (221) in 1%GO.WO3 as due to the heterojunction formed between GO and WO3 may also increase the electron transport in the gas-sensing process.